Footbridge usage in high-traffic flow highways: The intersection of safety and security in pedestrian decision-making - Oviedo-Trespalacios, Oscar; Scott-Parker, Bridie (Transportation research. Part F, Traffic psychology and behaviour, 2017)
•Explored pedestrian highway crossing behaviour via footbridge and ground.•Majority reported ground crossing was dangerous, but one third never or rarely used footbridge.•While perceived security increases safe crossing, positive safety attitudes reduces safe crossing.•The engineering solution of the nearby footbridge was an insufficient intervention for pedestrians. In the Decade of Action for Road Safety, the vulnerability of pedestrians to severe outcomes from road crash is well-recognised. This study explored the factors that are influential in pedestrians’ decisions to cross a high-traffic highway in Barranquilla, Colombia, by using a footbridge over the highway, or by cutting across the highway in close proximity to a footbridge. Participants were recruited at each crossing (n=105 footbridge, n=105 ground; n=117 males; M(SD) age=23.28(5.98) years) and completed a paper survey exploring demographics, highway crossing behaviour, and attitudes regarding the safety and security of the crossing. Despite the majority of participants reporting the ground crossing was dangerous, and that the footbridge crossing was safe, one third of participants never or rarely (approximately 0% and 25% of the time) used the footbridge to cross the highway. Logistic regression revealed that the decision regarding the highway crossing mode (footbridge or ground) was predicted by (a) the frequency in which the footbridge is crossed, (b) the perception of footbridge security in relation to crime, (c) the perception of footbridge safety about traffic conflicts in general, (d) the proximity of the footbridge to the highway ground crossing, and (e) if the subject had experienced an injury during a previous highway crossing. The findings extend our understanding of pedestrian behaviour in crossing highways, not only in relation to the use of footbridges which separate both road user groups, but also ground crossings which place the pedestrians at significant risk especially those in areas with high traffic flow density. Moreover, the findings highlight the complexity involved in improving pedestrian road safety, particularly as the provision of an engineering solution (a footbridge) in close proximity to a high-risk zone (highway) is clearly not the only solution in the much larger road safety system.